PENERAPAN METODE MEMBACA NYARING UNTUK MENINGKATKAN KEMAMPUAN MEMBACA SISWA KELAS 1 SD NEGERI PURWAKARTA I - Alifa Husnussyifa; Siti Rokmanah; Alifa Husnussyifa (STKIP Subang, 2023)
Abstract Reading ability is a child's ability to recognize letters and words, then connect them with sounds, and understand the meaning of the writing they read, which begins with the ability to hear the letters correctly and precisely. The reading aloud method or reading aloud is an activity carried out to improve reading and listening skills. Because with this method all students in the class will pay attention to the reading material and it can be a stimulant for students. This study used descriptive qualitative method. The qualitative descriptive method is a form of research aimed at describing or illustrating existing phenomena, both natural phenomena and human engineering. The data collection techniques used were interviews, observation and documentation, with the subjects being class I students at SD Negeri Purwakarta I, totaling 33 students. The results of this research show that applying the reading aloud method can effectively improve students' reading abilities. Keywords: Reading Ability, Reading Aloud Method